2015
DOI: 10.1007/s11547-015-0616-z
|View full text |Cite
|
Sign up to set email alerts
|

Management of radiation therapy patients with cardiac defibrillator or pacemaker

Abstract: The increasing growth of population with cardiac implantable electronic devices (CIEDs) such as Pacemaker (PM) and Implantable Cardiac Defibrillators (ICD), requires particular attention in management of patients needing radiation treatment. This paper updates and summarizes some recommendations from different international guidelines. Ionizing radiation and/or electromagnetic interferences could cause device failure. Current approaches to treatment in patients who have these devices vary among radiation oncol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 23 publications
0
33
0
2
Order By: Relevance
“…High photon energy of >10 MV makes it possible to produce neutrons, which affects the function of CIEDs, and Salerno et al recommended the application of low energy of ≤6 MV [16]. Gelblum et al .…”
Section: Discussionmentioning
confidence: 99%
“…High photon energy of >10 MV makes it possible to produce neutrons, which affects the function of CIEDs, and Salerno et al recommended the application of low energy of ≤6 MV [16]. Gelblum et al .…”
Section: Discussionmentioning
confidence: 99%
“…The potential interactions between high doses of radiation and the function, longevity, and integrity of the CIEDs, as well as the harm to the patients, remain unclear. The results of a recent review [60,61] showed that the risk of device failure increases with increasing radiation doses, without a clear cutoff point. For patients with pacemakers, the delivered total radiation dose to the device was strongly recommended not to exceed 2 Gy and the dose in patients with implantable cardiac defibrillators should be within 1 Gy.…”
Section: Radiation For Patients With Cardiac Implantable Electronic Dmentioning
confidence: 99%
“…Ionizing radiation exposure of 10 Gy can damage the random access memory of CIEDs used in programming and interrogation. 24 Salerno et al 24 recommend that, in general, ionizing radiation photonic energy be kept below 6 mV, and that therapeutic radiation to the head and neck region not exceed 2-10 Gy. In another study, 69 patients were studied for evidence of CIED interference or malfunction during radiation therapy.…”
Section: Radiationmentioning
confidence: 99%